Steam requirements and mass balance in digesters and screw presses at palm oil mill - Zulfatri Aini; Tengku, Tengku Reza Suka Alaqsa; Sri Basriati (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2024)
Fresh Fruit Bunches (FFB) are the primary component in Crude Palm Oil (CPO) production. Palm oil mills face challenges in optimizing CPO yield, particularly in reducing oil losses during processing, which affects efficiency and profitability. The pressing station, including the digester and screw press, plays an important role in oil extraction. The digester uses steam to heat and soften the fruit for better oil release, while the screw press performs the mechanical extraction of oil. Insufficient steam can hinder oil separation, leading to increased losses. This research aimed to analyze steam requirements for the digester and evaluate the mass balance of the screw press. Using energy and mass balance methods, the optimal steam requirement was 359,870 kg/hour with a mass balance error of 6.58%. Corrective actions in steam valve settings reduced oil losses to 1.57%, which improved processing efficiency and product quality.